Making meaning out of mountains : the political ecology of skiing - Stoddart, Mark C. J., 1974- (UBC Press, 2012)
"Mountains bear the imprint of human activity. Deep scars from logging and surface mining crosscut the landmarks of sports and recreation -- national parks and lookout areas, ski slopes and lodges. Although the environmental effects of extractive industries are well known, skiing is more likely to bring to mind images of luxury, wealth, and health. In Making Meaning out of Mountains, Mark Stoddart draws on interviews, field observations, and media analysis to explore how the ski industry in British Columbia has helped transform mountain environments and, in turn, how skiing has come to be inscribed with multiple, often conflicted meanings informed by power struggles rooted in race, class, and gender. Corporate leaders promote the skiing industry as sustainable development, while environmentalists and some First Nations argue that skiing sacrifices wildlife habitats and traditional lands to tourism and corporate gain. Skiers themselves appreciate the opportunity to commune with nature but are concerned about skiing's environmental effects. Stoddart not only challenges us to reflect more seriously on skiing's negative impact on mountain environments, he also reveals how certain groups came to be viewed as the "natural" inhabitants and legitimate managers of mountain environments."--Pub. desc.